Captive diet does not influence exploration behavior upon reintroduction to the wild in a critically endangered amphibian - Kelleher, Shannon R.; Silla, Aimee J.; Hunter, David A.; McFadden, Michael S.; Byrne, Phillip G. (Frontiers in Conservation Science, 2022)
Exploration behaviour can have profound effects on individual fitness. Consequently, knowledge of the proximate mechanisms underpinning exploration behaviour may inform conservation breeding programs (CBPs) for threatened species. However, the environmental factors that influence exploration behaviour in captivity and during the reintroduction process remain poorly understood. Dietary micronutrients, such as carotenoids, are known to affect the expression of energetically costly behavioural traits, and theoretically may also influence the degree of exploration behaviour in various contexts. Here, we investigate whether dietary β-carotene supplementation in captivity influences exploration behaviour upon reintroduction to the wild in the critically endangered southern corroboree frog, Pseudophryne corroboree. We conducted a manipulative dietary experiment where captive bred P. corroboree were supplemented with different doses of β-carotene for 40 weeks prior to release. Frogs (n = 115) were reintroduced to the wild using a soft-release approach, where they were released into field enclosures specifically designed for this species. Upon reintroduction, the frogs’ initial exploration behaviour was measured using a standardised behavioural assay. There was no effect of diet treatment on any measure of exploration behaviour (mean latency to leave the initial refuge, time spent mobile within the release apparatus and latency to disperse into the field enclosure). However, there was a significant relationship between individual body size and latency to leave the refuge, whereby smaller individuals left the refuge more rapidly. While these findings provide no evidence that β-carotene at the dosages tested influences P. corroboree exploration behaviour in a reintroduction context, the effect of body size draws attention to the potential for bodily state to influence exploration behaviour. We discuss the need for ongoing research investigating the influence of captive diet on post release behaviour, and highlight how knowledge concerning state-dependent behaviour might help to inform and direct reintroduction programs.